Використання спеціальних знань у галузі економіки під час розслідування злочинів у сфері службової діяльності - Пчеліна, О. В.; Pchelina, O. V.; Пчеліна Оксана Василівна (Часопис Національного університету "Острозька академія". Серія: Право. – 2014. – № 2(10), 2014)
У статті розкривається зміст поняття спеціальних знань. Обґрунтовується необхідність використання спеціальних економічних знань під час розслідування злочинів у сфері службової діяльності. Висвітлюються основні форми використання спеціальних знань у галузі економіки під час досудового розслідування окреслених злочинів.

Most crimes in the sphere of service activity are committed by officers using their position, influence, relationships and so on. Moreover, a large proportion of these crimes aimed at acquisition of some material possessions. Accordingly, a large amount of trace pattern will be reflected in all sorts of documents, including accounting and financial reporting. In addition, methods of committing outlined crimes are implemented through various business transactions. And, therefore, the investigator need expert help on economic issues. Because without such help the criminal proceedings will be ineffective. In this regard the article reveals the meaning of special knowledge. The necessity of using special economic knowledge in the investigation of crimes related to service activity is substantiated. The basic forms of using specialized knowledge in economics during the preliminary investigation of outlined crimes are highlighted.

В статье раскрывается содержание понятия специальных знаний. Обосновывается необходимость использования специальных экономических знаний при расследовании преступлений в сфере служебной деятельности. Освещаются основные формы использования специальных знаний в области экономики в ходе досудебного расследования определенных преступлений.
Использование специальных знаний в области экономики при расследовании преступлений в сфере служебной деятельности
Use special knowledge in the field of economics during the investigation of crimes related service activity
Keywords: Криміналістика. Criminalistics. Криминалистика; Наукові публікації. Scientific publications. Научные публикации; Україна. Ukraine. Украина; спеціальні знання; галузь економічних знань; злочини у сфері службової діяльності; досудове розслідування; special knowledge; economic knowledge; crimes related service activity; pre-trial investigation; специальные знания; отрасль экономических знаний; преступления в сфере служебной деятельности; досудебное расследование